Development and evaluation antitumor activity of PEGylated liposomal doxorubicin on tumor-bearing BALB/c-Foxn1nu mice model - Hue Pham Thi Minh, Linh Le Phuong, Hai Nguyen Thanh, Son Ho Anh, Tung Bui Thanh (Journal of Applied Pharmaceutical Science, 2015)
Doxorubicin hydrochloride is an antitumor antibiotic derived from anthracyclines. It has had limited use because of its dose-related cardiotoxicity and myelosuppression. Liposomes have been used as a vehicle for administration of pharmaceutical drugs because of their ability to improve the delivery of drugs to tumors, increase therapeutic efficacy, and decrease toxicity to normal cells. The aim of this study is to prepare a new liposomal dxorubicin on a large-scale and evaluate its antitumor activity in vivo. Liposomes were formed using the hydration of a thin lipid film method, and doxorubicin was loaded through a pH gradient technique. Based on TEM images, large lamellar vesicles (LUV) were formed, with sizes of 95 ± 10 nm, having a polydispersity index of 0.138 ± 0.02 and zeta potentials of about -27.8 ± 2.15 mV. The entrapment efficiency was approximately 97%. The therapeutic activity of PEGylated liposomal doxorubicin formulations was studied on human colorectal carcinoma HT 29 tumor-bearing BALB/c-Foxn1nu mice models. Our results have shown that liposome preparation can reduce the tumor volume and increase the survival rate and survival time as compared with Lipo Dox. PEGylated liposomal doxorubicin demonstrated much stronger antitumor activities, and statistical differences were significant when compared with free doxorubicin.
Keywords: Doxorubicin, liposome, PEGylated, tumor-bearing mice, HT29.